A Descriptive Survey Study of International Students’ Experiences at a Canadian University: Challenges, Supports, and Suggested Improvements - Worae, Jonathan; Edgerton, Jason (Comparative and International Education / Éducation comparée et internationale, 2023)
The current descriptive survey study focuses on international students’ experiences—challenges, personal and institutional supports—during their studies at a Canadian university, as well as their suggestions for what additional supports they think would be helpful. An online survey (n = 712) examined international students challenges within a number of domains: language, financial, academic, environmental and cultural, personal- social, and discrimination. The majority of the international students reported few language and academic challenges, but many reported financial and personal-social challenges. COVID-19 presented additional challenges for most international students. Student use of various coping strategies (e.g., staying in touch with family) and institutional supports (e.g., international students centre) were also examined. Bivariate analyses revealed that students under 30 (vs. 30 or over), students who had been in Canada for more than 2 years (vs. 2 years or less), and undergraduates (vs. graduates) were more likely to report various challenges and that undergraduate students and female students were more likely to seek academic guidance and counselling services. The importance of promoting awareness of, and increasing culturally attuned provision of, counselling services is discussed. Finally, summarizing the suggestions of student respondents, a number of recommendations are made regarding how to improve supports for international students.